EDUCATION POLITICS IN ISLAMIC BOARDING SCHOOL AND MADRASA: The Old Order, The New Order, and The Reform Era - Jufri Naldo; Azhari Akmal Tarigan; Faisal Riza (AL-TAHRIR, 2020)
Abstract: The development of Islamic boarding schools and madrasas in Indonesia cannot be separated from the political education policy of the government that is currently in power. Through a literature study, this study intends to reveal how the form of education politics carried out by the government towards these two institutions. The theoretical debate on education politics during the Old Order begins the explanation of this study. Then, the debate during the New Order is discussed, and the debate related to the Reformation era is discussed after that. This study illustrates that despite the politicization of Islamic boarding schools and madrasas, these indigenous Indonesian educational institutions must be preserved and their development should be considered. Furthermore, Islamic boarding schools and madrasas are important indicators for the progress of the religion and the nation. By looking at the realities of advanced education today, Islamic boarding schools and madrasas are a reflection of the superiority of scientific, intellectual, and cultural achievements. The government as a policymaker should provide full political support so that Islamic boarding schools and madrasas can compete at the world level.الملخص: لا يمكن فصل تطوير المدارس الداخلية الإسلامية والمدارس الدينية في إندونيسيا عن سياسة التعليم السياسي للحكومة التي تتولى السلطة حاليًا. تهدف هذه الدراسة ، من خلال دراسة أدبية ، إلى الكشف عن شكل السياسة التربوية التي تنفذها الحكومة تجاه هاتين المؤسستين. سيبدأ النقاش النظري حول سياسات التعليم في عهد النظام القديم في شرح هذه الدراسة ، ثم يتبعها في عهد النظام الجديد ، وينتهي خلال فترة الإصلاح. توضح هذه الدراسة أنه على الرغم من تسييس المدارس الداخلية الإسلامية والمدارس الدينية ، يجب الحفاظ على هذه المؤسسات التعليمية الإندونيسية الأصلية والنظر في تطويرها. علاوة على ذلك ، فإن المدارس الداخلية الإسلامية هي مؤشرات مهمة لتقدم الدين والأمة. بالنظر إلى واقع التعليم المتقدم حاليًا ، فإن المدارس الداخلية الإسلامية والمدارس الإسلامية هي انعكاس لتفوق الإنجازات العلمية والفكرية والثقافية. يجب على الحكومة كصانع للسياسة أن تقدم الدعم السياسي الكامل حتى تتمكن المدارس الداخلية الإسلامية والمدارس الإسلامية من المنافسة على المستوى العالمي.Abstrak: Perkembangan Pesantren dan madrasah di Indonesia tidak dapat dipisahkan dari kebijakan politik pendidikan pemerintah yang sedang berkuasa. Melalui studi literatur, kajian ini hendak mengungkap bagaimana bentuk politik pendidikan yang dijalankan oleh pemerintah terhadap kedua lembaga tersebut. Perdebatan teoritis politik pendidikan pada masa Orde Lama akan mengawali penjelasan kajian ini, kemudian disusul pada masa Orde Baru, dan diakhiri pada masa Reformasi. Kajian ini memberikan gambaran bahwa sekalipun terjadi politisasi terhadap pesantren dan madrasah, akan tetapi lembaga pendidikan asli Indonesia ini harus tetap dilestarikan dan diperhatikan perkembangannya. Selanjutnya, pesantren dan madrasah merupakan salah satu indikator penting untuk kemajuan agama dan bangsa. Dengan melihat realitas pendidikan yang sudah maju saat ini, pesantren dan madrasah adalah cerminan dari keunggulan capaian keilmuan, intelektual dan kultural. Pemerintah sebagai pemangku kebijakans udah sepatutnya memberikan dukungan penuh secara politik agar pesantren dan madrasah bisa bersaing di tingkat dunia.